2021
DOI: 10.1002/ima.22566
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional capsule network for COVID‐19 detection using radiography images

Abstract: Novel corona virus COVID‐19 has spread rapidly all over the world. Due to increasing COVID‐19 cases, there is a dearth of testing kits. Therefore, there is a severe need for an automatic recognition system as a solution to reduce the spreading of the COVID‐19 virus. This work offers a decision support system based on the X‐ray image to diagnose the presence of the COVID‐19 virus. A deep learning‐based computer‐aided decision support system will be capable to differentiate between COVID‐19 and pneumonia. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…The papers reported in [12] implemented as pre-trained CNNs for the detection of COVID-19 from x-ray images, such as MobileNet-v2 [13] , ResNet-v2 [14] VGG-19 [15] and Inception [16] . The two pretraining CNNs used two data sets, which consisted of COVID-19 images, viral pneumonia, bacterial pneumonia, and solid conditions, in the case of 2 and 3 classifications.…”
Section: Literature Surveymentioning
confidence: 99%
“…The papers reported in [12] implemented as pre-trained CNNs for the detection of COVID-19 from x-ray images, such as MobileNet-v2 [13] , ResNet-v2 [14] VGG-19 [15] and Inception [16] . The two pretraining CNNs used two data sets, which consisted of COVID-19 images, viral pneumonia, bacterial pneumonia, and solid conditions, in the case of 2 and 3 classifications.…”
Section: Literature Surveymentioning
confidence: 99%
“…CNN is one such type of deep neural network, which is also known as the ConvNet model. It mainly comprises three layers, namely (1) convolution layer, (2) pooling layer, and (3) dense layer (fully connected layer) [31]- [32]. The first layer i.e., the convolutional layer, is an essential building block of ConvNet.…”
Section: Convolutional Neural Network (Convnet)mentioning
confidence: 99%
“…Authors conclude that their presented model with more than 96% score (in all parameters like Precision, Recall, F-Score, Specificity and Accuracy). In just recently published study researchers, Tiwari et al [ 42 ] suggested a system based on visual geometry group capsule network (VGG-CapsNet) to screen COVID-19 disease based on input images. The composed dataset contains around 2900 images belonging to three classes (normal, pneumonia and COVID-19).…”
Section: Introductionmentioning
confidence: 99%